Pengaruh Struktur Kepemilikan, Penerapan Digital Banking, dan Investasi Teknologi Informasi terhadap Kinerja Intellectual Capital: Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2017-2021 - Oktavillia, Annisa; Afriyenti, Mayar (Jurnal Nuansa Karya Akuntansi, 2024)
The study aims to prove the effect of the implementation of digital banking, investment in information technology, and ownership structure such as institutional ownership and foreign ownership on intellectual capital performance. The population in this study was banking sector company in Indonesia Stock Exchange in 2017- 2021. Sample was determined using the purposive sampling method. Data analysis technique for hypothesis testing using multiple regression analysis. The of statistical analysis show that foreign ownership has no significant effect while institutional ownership, the implementation of digital banking, and investment in information technology have positive and significant effect to intellectual capital performance.